Infarct size and left ventricular remodelling after preventive percutaneous coronary intervention. Issue 24 (8th August 2016) - Mangion, Kenneth; Carrick, David; Hennigan, Barry W; Payne, Alexander R; McClure, John; Mason, Maureen; Das, Rajiv; Wilson, Rebecca; Edwards, Richard J; Petrie, Mark C; McEntegart, Margaret; Eteiba, Hany; et al.
Abstract : Objective: We hypothesised that, compared with culprit-only primary percutaneous coronary intervention (PCI), additional preventive PCI in selected patients with ST-elevation myocardial infarction with multivessel disease would not be associated with iatrogenic myocardial infarction, and would be associated with reductions in left ventricular (LV) volumes in the longer term. Methods: In the preventive angioplasty in myocardial infarction trial (PRAMI; ISRCTN73028481 ), cardiac magnetic resonance (CMR) was prespecified in two centres and performed (median, IQR) 3 (1, 5) and 209 (189, 957) days after primary PCI. Results: From 219 enrolled patients in two sites, 84% underwent CMR. 42 (50%) were randomised to culprit-artery-only PCI and 42 (50%) were randomised to preventive PCI. Follow-up CMR scans were available in 72 (86%) patients. There were two (4.8%) cases of procedure-related myocardial infarction in the preventive PCI group. The culprit-artery-only group had a higher proportion of anterior myocardial infarctions (MIs) (55% vs 24%). Infarct sizes (% LV mass) at baseline and follow-up were similar. At follow-up, there was no difference in LV ejection fraction (%, median (IQR), (culprit-artery-only PCI vs preventive PCI) 51.7 (42.9, 60.2) vs 54.4 (49.3, 62.8), p=0.23), LV end-diastolic volume (mL/m 2, 69.3 (59.4, 79.9) vs 66.1 (54.7, 73.7), p=0.48) and LV end-systolic volume (mL/m 2, 31.8 (24.4, 43.0) vs 30.7 (23.0, 36.3), p=0.20). Non-culprit angiographic lesions had low-risk Syntax scores and 47% had non-complex characteristics. Conclusions: Compared with culprit-only PCI, non-infarct-artery MI in the preventive PCI strategy was uncommon and LV volumes and ejection fraction were similar.